FARMERS’ PERCEPTION OF POVERTY AND WELFARE IN BOKI LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - Eneji, Rosemary I.; Frank, Attah (International Journal of Research -GRANTHAALAYAH, 2018)
The worsening state of poverty among rural farmers in Nigeria’s Cross River State has attracted great concern from government and its agencies but farmers’ perception of poverty and welfare is little understood. In this study, it was determined whether and how the social variables of income, healthcare and education affect farmers’ perception of poverty and welfare in Boki Local government area. Primary data were derived from one hundred (100) respondents, randomly drawn from the study area using standard questionnaires and analysed using the chi-square technique. There was a significant direct relationship between income level, health care, education and nutrition on one hand and welfare of farmers on the other. Evidence from this field study strongly suggests that poverty alleviation programmes and infrastructural projects should be extended to rural areas for improved welfare and livelihood. However, farmers do not necessarily perceive poverty based only on the variables studied.